Income vs. Consumption Inequality in South Korea: Evaluating Stochastic Dominance Rankings by Various Household Attributes - Almas Heshmati; Robert Rudolf (Institute for the Study of Labor (IZA), 2013)
Using four rounds (1999, 2002, 2005, 2008) of the Korean Labor and Income Panel Study (KLIPS), this article examines determinants of household income and consumption levels and inequalities. Unconditional as well as conditional stochastic dominance (SD) tests are performed by year, by household heads' characteristics (age, education, gender, health, marital status and occupation) and by household characteristics (household type, household size, degree of urbanization). Mean least squares regression techniques are employed to predict conditional expectations. The residuals containing effects for each characteristic conditional on the remaining characteristics are then used for the SD analysis employing extended Kolmogorov-Smirnov tests of first- and second-order dominance in distribution of income and consumption. The results provide a detailed and up-to-date picture of inequality and poverty by subgroup in South Korea which helps targeting particularly vulnerable groups. Overall, while inequality in disposable income is found to be often substantial, strong savings preferences of richer households lead to relatively low consumption inequality. Households headed by elderly, uneducated, divorced or widowed, females and those with health problems are found to be the most vulnerable groups in Korea.
Keywords: D63; D31; I31; C14; 330; stochastic dominance; bootstrap; disposable income; consumption inequality; poverty; South Korea